2021
DOI: 10.3390/curroncol28030209
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Treatment with a Cyclin-Dependent Kinase 4/6 Inhibitor Plus an Aromatase Inhibitor for Metastatic Breast Cancer in Alberta

Abstract: In this analysis, we describe population-based outcomes for first-line treatment with a cyclin-dependent kinase 4/6 inhibitor (CDK4/6i) combined with an aromatase inhibitor (AI). All patients who were prescribed CDK4/6i + AI from January 2016 through June 2019 were included. Patient demographics, tumour and treatment characteristics were collected and described. Survival distributions were estimated using the Kaplan–Meier method. Multivariate analysis (MVA) was constructed to examine associations between poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…This retrospective real-world study utilized the Syapse LHN to identify patients with HR+/HER2− A/MBC who were treated with palbociclib plus an aromatase inhibitor as first-line therapy. Findings from this study indicate treatment patterns and effectiveness outcomes with palbociclib plus aromatase inhibitor combination therapy are similar to what has been observed in other EHR real-world studies and complement data from randomized controlled trials [ 8 , 9 , 11 , 19 , 26 , 27 , 28 , 29 , 30 ]. After a median follow-up duration of 22.4 months, median rwPFS was 31.7 months and the estimated OS rate at 2 years was 78.0%.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This retrospective real-world study utilized the Syapse LHN to identify patients with HR+/HER2− A/MBC who were treated with palbociclib plus an aromatase inhibitor as first-line therapy. Findings from this study indicate treatment patterns and effectiveness outcomes with palbociclib plus aromatase inhibitor combination therapy are similar to what has been observed in other EHR real-world studies and complement data from randomized controlled trials [ 8 , 9 , 11 , 19 , 26 , 27 , 28 , 29 , 30 ]. After a median follow-up duration of 22.4 months, median rwPFS was 31.7 months and the estimated OS rate at 2 years was 78.0%.…”
Section: Discussionsupporting
confidence: 82%
“…Previous real-world studies showed a median rwPFS between 15.1 and 37.9 months with palbociclib combination therapy as first-line therapy for HR+/HER2− A/MBC [ 19 , 26 , 27 , 28 , 29 , 30 ]. The median rwPFS outcome observed in the current real-world study is longer than some PFS estimates previously reported; this may be due in part to the better overall prognostic characteristics of the patients in this cohort, with a larger proportion of patients with de novo disease and bone-only disease, which tends to be associated with longer PFS [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our results with both letrozole and fulvestrant suggest a substantial benefit of palbociclib on PFS in women with HR-positive, HER2−negative metastatic breast cancer in a Canadian context, as observed in the existing literature [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Study Results In the Context Of Existing Literaturesupporting
confidence: 74%
“…The findings of this study contribute to the growing literature of real-world evidence with palbociclib from a Canadian context [17,18,32]. To the best of our knowledge, this is one of the first studies of its kind designed to investigate the effect of alternative dosing strategies on progression-free survival.…”
Section: Study Results In the Context Of Existing Literaturementioning
confidence: 67%
See 1 more Smart Citation